How do you counsel distance students in higher education programme. - Mat Zin, Ab.Rasid
In the pursuit of higher education, distance students face many obstacles which they have to manage very tactfully in order to gain maximum benefit and success in their studies. For example, some students experience family problems, other students have hard time with finance, and yet some other students have work related problems, personal problems as well as problems in coping with student life. These problems are evidenced in our day-to-day involvement with distance students and also verified by some questionnaire surveys.